Correlation of Recruitment and Selection of Human Resources and the Performance of Small and Medium Enterprises - Klepić, Iva (Naše gospodarstvo/Our economy, 2019)
Human resources are the most significant resource of a company; this is especially true for small and medium enterprises (SMEs) in which they create the company’s competitive advantage because of their uniqueness. Human resources manage other resources and are responsible for the efficiency and success of the organization. The main goal of this research is to determine whether and to what extent the recruitment and selection of human resources are in correlation with the performance of SMEs. The research was conducted in SMEs in the Herzegovina Region in the Federation of Bosnia and Herzegovina in April 2019. An original questionnaire was created for the survey, within which top managers views on recruitment and selection of human resources were collected as well as the four- perspective performance of the business based on the Balanced Scorecard model. SPSS 20.0 was used for data analysis. Descriptive measurements used for data analysis include mean, standard deviation, and mode. The Kolmogorov-Smirnov test was used to test distribution normality. To test the correlation of variables and to determine the significance of differences, the Pearson correlation coefficient and t-test for independent samples were used. The level of significance was set to p = 0.05. The research results showed the correlation between the studied variables and the correlation of recruitment and selection of human resources and the performance of SMEs viewed from all four perspectives. A limitation of the research is the sample size and the sampling method. The results can be applied in the human resource management of SMEs.